2018
DOI: 10.1007/s10711-018-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

Laminations from the symplectic double

Abstract: Let S be a compact oriented surface with boundary together with finitely many marked points on the boundary, and let S • be the same surface equipped with the opposite orientation. We consider the double S D obtained by gluing the surfaces S and S • along corresponding boundary components. We define a notion of lamination on the double and construct coordinates on the space of all such laminations. We show that this space of laminations is a tropical version of the symplectic double introduced by Fock and Gonc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Results of this paper were first reported by the first named author on the Nielsen Retreat of QGM,Århus University, 26-29 October 2014. Simultaneously, the papers [25] and [1] had appeared dealing with similar issues. In particular, Allegretti had also introduced additional shear-type variables associated to external edges of an ideal triangle decomposition of a bordered cusped Riemann surfaces and observed (Lemma 6.3 in [1]) the monoidal relation between exponentiated shear coordinates and λ-lengths.…”
Section: Resultsmentioning
confidence: 94%
“…Results of this paper were first reported by the first named author on the Nielsen Retreat of QGM,Århus University, 26-29 October 2014. Simultaneously, the papers [25] and [1] had appeared dealing with similar issues. In particular, Allegretti had also introduced additional shear-type variables associated to external edges of an ideal triangle decomposition of a bordered cusped Riemann surfaces and observed (Lemma 6.3 in [1]) the monoidal relation between exponentiated shear coordinates and λ-lengths.…”
Section: Resultsmentioning
confidence: 94%
“…Such a moduli space would have twice the dimension of X(S,M) and would be birational to the principal cluster variety . Closely related spaces associated to the symplectic double cluster variety were described in .…”
Section: Introductionmentioning
confidence: 99%
“…In [4], Fock and Goncharov showed that this space is closely related to the geometry of the doubled surface S D . In [1], the author studied versions of the Teichmüller space and space of measured laminations on S D which are closely related to the above construction. Definition 3.9 describes the moduli space D P GLm,S when there are no marked points on the boundary of S. To define this space for a general decorated surface, we must modify the definition slightly.…”
Section: The Symplectic Double Moduli Spacementioning
confidence: 99%
“…It was shown in [4] and [1] that this object is related to certain moduli spaces of geometric structures on a doubled surface. Given a compact oriented surface S with boundary, one considers the same surface S • with the opposite orientation.…”
Section: Introductionmentioning
confidence: 99%